Tahap keyakinan diri bekas penagih dadah dalam pengawasan di Malaysia : ke arah kepulihan menyeluruh (self-esteem among former drug addicts under observation in Malaysia: towards a comprehensive recovery) - Salina Nen; Fauziah Ibrahim; Ezarina Zakaria; Mohd Norahim Mohamed Sani; Nor Jana Saim (Penerbit Universiti Kebangsaan Malaysia, 2017)
Recovering drug addict is affected by two main factors, namely internal factors (such as resilience and self-confidence) and external (support from families, employers, friends, and community). One of the internal factors that appear to influence the level of recovery of former drug addict is self-confidence. Therefore this study aims to measure the level of self-confidence among former drug addicts, also known as Orang Kena Pengawasan (OKP) who underwent rehabilitation in 6-11 months and 12-24 months. The study was conducted using cross-sectional surveys. A total of 386 former drug addicts in Peninsular Malaysia were involved in this study with 198 respondents undergoing 6-11 months rehabilitation programme and 197 were respondents who were released within 12-24 months. The data obtained were analyzed using descriptive statistics. This analysis was used to measure the level of self-confidence between respondents who underwent the 6-11 months rehabilitation programme (Group 1) and 12-24 months (Group 2). The study found that the majority of both groups showed no signiticant difference in the level of recovery from the aspect of self-confidence. The study also found the majority of respondents of both groups showed a moderate level of confidence of 58.5 percent. However, Group 1 showed a higher percentage of self-confidence (63.5%) compared to Group 2 of (53.8%). The findings have implications for the development of strategies towards a strong self-confidence among the inmates to reduce recidivism rates in Malaysia.